Study of menstrual cycle in training load variability in female basketball players - Arenas-Pareja, M. Á.; Lopez-Sierra, P.; Ibáñez, S. J.; García-Rubio, J. (Journal of Human Sport & Exercise, 2026)
The menstrual cycle is a key factor influencing athletic performance. This study analysed its impact on the training load of female basketball players over a two-month period using a case series design with ten participants. Descriptive analysis, variation coefficients, mixed linear models, and regression techniques were applied to assess the relationship between menstrual phases and training variables. The results indicate that a significant portion of performance variability is linked to specific menstrual phases, with notable individual differences. Understanding these fluctuations is essential for optimizing training programs that align with athletes' physiological states. During phases of hormonal stability, such as the follicular phase, high-intensity training can be prioritized to maximize physical output, focusing on explosive movements, accelerations, and decelerations. Conversely, during the luteal or menstrual phase, when hormonal fluctuations may reduce fatigue tolerance, training should emphasize moderate-intensity or technical sessions to support recovery while maintaining performance. Incorporating menstrual cycle-aware training adaptations can improve athletic performance, reduce injury risk, and enhance overall well-being, underscoring the need for a more individualized approach to female athlete conditioning.